Effect of soya milk on nutritive, antioxidative, reological and textural properties of chocolate produced in a ball mill - Zarić Danica B.; Pajin Biljana S.; Rakin Marica B.; Šereš Zita I.; Dokić Ljubica P.; Tomić Jelena M. (Hemijska Industrija, 2011)
Chocolate is a complex rheological system in which non-fat cocoa particles and sugar particles are enveloped by crystal matrix of cocoa butter. Physical properties of chocolate depend on ingredient composition, method of production and properly performed pre-crystallization phase. In this work, chocolate was produced in an unconventional way, i.e. in a ball mill applying variable refining time (30, 60 and 90 min) and pre-crystallization temperature in chocolate masses (26, 28 and 30⁰C). Two types of chocolate were produced: chocolate with 20% of powdered cow’s milk (R1) and chocolate with 20% of soya milk powder (R2). The quality of chocolate was followed by comparing nutritive composition, 23 polyphenol content, hardness of chocolate, solid triglyceride content (SFC) and rheological parameters (Casson yield flow (Pa), Casson viscosity (Pas), the area of the thixotropic loop, elastic modulus and creep curves). The aim of this paper is determining changes caused by replacing cow’s milk with soya milk powder in respect of nutritive, rheological and sensory properties, as well as defining optimal parameters: precrystallization temperature and refining time of soya milk chocolate in order to obtain suitable sensory and physical properties identical to those of milk chocolate mass. The results show that replacing powdered cow’s milk with soya milk powder affects the increase in nutritive value of soya milk chocolate. R2 chocolate mass showed the increase in essential amino acids and fatty acids. This chocolate mass also showed the increase in total polyphenols by 28.1% comparing to R1 chocolate mass. By comparing viscosity, yield stress, shear stress and the area of the thixotropic loop, it can be observed that R1 chocolate mass represents a more organized and simpler system than the mass with soya milk (R2), as it shows lower values for all the above mentioned parameters, regardless of the refining time and pre-crystallization temperature. Viscoelastic behavior of R2 is also evident, as a consequence of soya protein presence. In order to maintain optimal hardness as well as melting resistance of chocolate, in case of R2 chocolate mass it is necessary to apply pre-crystallization temperature of 26⁰C, while for the chocolate mass R1 it is 30⁰C.